Caracterización del perfil hematológico y bioquímico del Ovino Criollo Ecuatoriano en la provincia de Bolívar. - Paucar Arcos, Franklin Patricio (2018)
This research was conducted in Bolivar Province specifically in Guaranda, located in the center of the country, the objective is to characterize the hematological and biochemical profile, as well as the plasma proteins; in addition, drawing a georeferencing map to locate each crossbred sheep Ecuadorian animals, encouraging scientific knowledge of the breed in Bolivar province, as a strategy to strengthen conservation programs for their animal population. Thirty animals were used and classified by sex (18female and 12 males animals) and age, different stages of development (young adults). Blood samples were taken by jugular venipuncture, prior asepsis and stored at a temperature of 8 ° C, for further transport. Blood sampling method automated quantification was used, the result of this data was statistically analyzed (ANOVA) with basic measures, arithmetic mean (average), standard deviation (Std. Deviations) which revealed in hematological, biochemical profile and plasma proteins. In the statistical analyzes classified by different stages of development (young adult) and sex securities issued by InfoStat, show a slight variation in the results, but it does not indicate significant difference in any hematological, biochemical parameter certainly not in the plasma proteins, maintaining the values in the normal range compared with other investigations. The parameters measured in the hematological profile are: hematocrit, hemoglobin, erythrocyte, mean corpuscular volume, mean corpuscular hemoglobin, mean corpuscular hemoglobin concentration. The biochemical parameters were analyzed as follows: glucose, urea, blood urea nitrogen, creatinine, AST, ALT and plasma proteins.